PERAN FASILITAS KEAGAMAAN DALAM MEMBENTUK KEDISIPLINAN IBADAH SANTRI DI PONDOK PESANTREN AL-IKHLAS PROKLAMASI KARAWANG - Albi, Khaerul Financy; Bariah, Oyoh; Kholifah, Afiyatun (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to describe the role of religious facilities in shaping the worship discipline of santri (students) at Al-Ikhlas Islamic Boarding School (Pondok Pesantren), Proklamasi Karawang. A qualitative research method with a case study approach was employed. Data were collected through observation, in-depth interviews, and documentation involving the school's clerics, teachers, and students. The findings reveal that the quality of religious facilities including the condition of the mosque, ablution areas, prayer equipment, cleanliness, and the overall comfort of the worship environment plays a significant role in forming disciplined worship habits among santri. Adequate facilities create a conducive worship environment, increase students' motivation to participate on time, and reinforce congregational prayer routines. Conversely, facility limitations such as insufficient mosque capacity and poorly maintained ablution areas potentially hinder the development of worship discipline. This study recommends improving the quality and management of religious facilities as an integral part of strategies to foster santri worship discipline in Islamic boarding schools.